Effect of L-carnitine supplementation on maturation and early embryo development of immature mouse oocytes selected by brilliant cresyle blue staining - Zare, Zohreh (J Assist Reprod Genet, 2015)
PURPOSE: The present study was designed to investigate the effect of L-carnitine treatment during IVM on nuclear and cytoplasmic maturation of immature oocytes selected by Brilliant Cresyle Blue (BCB) staining, and their subsequent developmental competence. MATERIALS & METHODS: Compact cumulus-oocyte complexes (COCs) were collected from NMRI mice ovaries and stained with BCB staining. BCB+ (colored cytoplasm) oocytes were then cultured in tissue culture medium (TCM) 199 with 0.0, 0.3 and 0.6 mg/ml L-carnitine. RESULTS: The both L-carnitine concentrations significantly increased the intracellular glutathione (P < 0.001), nuclear maturation (P < 0.01) and expression levels of cyclin-dependent kinase1 (CDK1) (P < 0.05). Moreover, treated oocytes with 0.6 mg/ml L-carnitine showed increased (P < 0.05) expression of mitogen-activated protein kinase1 (MAPK1) mRNA. Also, adding L-carnitine (0.6 mg/ml) to IVM medium significantly increased the cleavage rate (P < 0.05). The blastocyst development rate (BDR) in the both L-carnitine treated groups was significantly higher (P < 0.001) than the control group. L-carnitine had no significant effect on total blastocyst cell numbers. CONCLUSIONS: These data indicated that L-carnitine supplementation during IVM of immature BCB+ oocytes improved preimplantation developmental competence of oocytes after IVF, probably by accelerating cytoplasmic and nuclear maturation of oocytes. It may provide a novel approach to improving ART outcomes in infertile couples.